Improving glycaemic control in type 2 diabetes: Stimulate insulin secretion or provide beta‐cell rest?. Issue 9 (10th July 2017) - van Raalte, Daniël H.; Verchere, C. Bruce
Abstract : Type 2 diabetes (T2D) is characterized by a gradual decline in pancreatic beta cell function that determines the progressive course of the disease. While beta‐cell failure is an important contributor to hyperglycaemia, chronic hyperglycaemia itself is also detrimental for beta‐cell function, probably by inducing prolonged secretory stress on the beta cell as well as through direct glucotoxic mechanisms that have not been fully defined. For years, research has been carried out in search of therapies targeting hyperglycaemia that preserve long‐term beta‐cell function in T2D, a quest that is still ongoing. Current strategies aim to improve glycaemic control, either by promoting endogenous insulin secretion, such as sulfonylureas, or by mechanisms that may impact the beta cell indirectly, for example, providing beta‐cell rest through insulin treatment. Although overall long‐term success is limited with currently available interventions, in this review we argue that strategies that induce beta‐cell rest have considerable potential to preserve long‐term beta‐cell function. This is based on laboratory‐based studies involving human islets as well as clinical studies employing intensive insulin therapy, thiazolidinediones, bariatric surgery, short‐acting glucagon‐like peptide (GLP)‐1 receptor agonists and a promising new class of diabetes drugs, sodium‐glucose‐linked transporter (SGLT)‐2 inhibitors. Nevertheless, a lack of long‐term clinical studies that focus on beta‐cell function for the newer glucose‐lowering agents, as well as commonly used combination therapies, preclude a straightforward conclusion; this gap in our knowledge should be a focus of future studies.